Fumigation of imported Tectona grandis and southern yellow pine with Pongamia pinnata seed oil against sapstain and mould - Sahu, Anamika; Tripathi, Sadhna; Ganguly, Sauradipta; Sumi, Akhato (Maderas. Ciencia y Tecnología, 2021)
An eco-friendly alternative of Pongamia pinnata seed oil was tested for fumigation of imported Tectona grandis and Pinus spp. (Southern yellow pine) against sap stain and mould fungi at 25 ± 2 and 75 % ± 5 % relative humidity.Veneeer and block samples of both species, and Petri dishes with agar media were fumigated with three different concentrations (w/v) of Pongamia pinnata seed oil and exhibited significant inhibition of fungal growth in comparison to the control sets, with the highest concentration of 6,4 g/ 8 mL3 proving to be the most lethal. Tectona grandis exhibited no infestation of sapstain and mould in either type of specimens whereas highly perishable Southern yellow pine displayed slight infestation of 4 % and 5 % with 1,6 g/ 2 mL3 of Pongamia pinnata seed oil for venner and block specimens as compared to 18 % and 20 % infestation observed in respective controls.The infestation on Southern yellow pine reduced to 1 % and 2 % respectively for veneers and blocks with 4 g/ 5 mL3 of Pongamia pinnata seed oil and was completely inhibited at 6,4 g/ 8 mL3 for both type of Southern yellow pine specimens. Petri plates returned similar findings where all higher concentrations inhibited mould growth completely and the lowest concentration exhibited meagre mould growth. Sapstain was inhibited successfully by all three concentrations of Pongamia pinnata seed oil on agar media.